Rodowitym rytmem pracy Janickiego dopełniam” „Vitae Regum Polonorum” Klemensa Janickiego w przekładzie Jana Bielskiego - Mieszek, Małgorzata (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2014)
The article is analysing literary portraits of Polish kings, which Jan Bielski took from the Vitae Regum Polonorum by Klemens Janicki. The Jesuit placed those short poems in his book Widok Królestwa Polskiego — a kind of history and geography textbook. Bielski’s paraphrases supplemented most chapters of the book, constituted the poetic summary and at the same time enable to formulate the evaluation of kings. Bielski’s poems are most often a faithful paraphrase, preserving the plot of the original. The Jesuit made only a few changes. Most of them reveal on the stylistic plain, rarely on the content plain.